Metal Complexes of Bispidine Derivatives: Achievements and Prospects for the Future - Altynay B. Kaldybayeva; Valentina K. Yu; Feyyaz Durap; Murat Aydemir; Khaidar S. Tassibekov (Molecules, 2025)
Multidentate bispidine ligands, including tetra-, penta-, hexa-, hepta-, and octadentate variants, exhibit strong coordination tendencies due to their intrinsic rigidity, significant reorganization potential, and ability to efficiently encapsulate metal ions. These structural attributes profoundly influence the thermodynamic stability, metal ion selectivity, redox behavior, and spin-state configuration of the resulting complexes. Metal ions, in turn, serve as highly suitable candidates for coordination due to their remarkable kinetic inertness, rapid complex formation kinetics, and low redox potential. This review focuses on ligands incorporating the bispidine core (3,7-diazabicyclo[3.3.1]nonane) and provides an overview of advancements in the synthesis of metal complexes involving p-, d-, and f-block elements. Furthermore, the rationale behind the growing interest in bispidine-based complexes for applications in radiopharmaceuticals, medicinal chemistry, and organic synthesis is explored, particularly in the context of their potential for diagnostic and catalytic drug development.